Aspectos do processo de colaboração compositor-intérprete na composição e interpretação da obra Espelhos das (In)tolerâncias de Marcílio Onofre para violoncelo solo e grupo de violoncelos - Borges, Rodolpho Cavalcanti (2018)
It presents the collaborative process between interpreter / composer in the composition and interpretation of the work Espelhos das (In)tolerâncias, of the composer Marcílio Onofre, commissioned by Rodolpho Borges. Thus, the related problematic will be treated focusing on some technical aspects of the execution of the Work, such as the different scordaturas, the use of multiphonics and tonlos. Therefore, broaches and analyzes the construction of the piece, not only in the part of the solo cello, but in the totality of the voices that compose the Work, that is, it drafts the main points, where, in fact, occur the dynamics of this process, where and when the performer assists in the construction of the piece, suggesting and proposing feasible solutions, sharing his technical-instrumental knowledge and allowing the composer all the technical field in the creation of the piece for the cello. The methodological procedure was based on the understandings of Cardassi (2016), Domenici (2011) and Borém (1998) that deal with the composer-interpreter relationship. There were also 6 interviews and meetings between the composer and the performer, as well as rehearsals, recordings and public performances of the piece. At the end of this process, it was concluded that this partnership provides different technical and musical possibilities for composers and performers.